KEDUDUKAN REKAM MEDIS DALAM PEMBUKTIAN MALPRAKTIK BERDASARKAN UNDANG-UNDANG NOMOR 36 TAHUN 2009 TENTANG KESEHATAN - Sri Pagitnita Tarigan Sibero; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Health has a very important meaning for everyone. Health becomes something coveted by everyone. Many ways are then performed in order to stay healthy, ranging from the adoption of healthy lifestyles (as preventive measures), to go to the doctor when the disease (as a repressive). When a person's health is compromised, they will do a variety of ways to be healthy again as soon as possible. Treatment to the doctor is an option when a person (patient) suffering from a disease. The hope is that they experienced disease can be cured by the doctor. From the research results can be concluded that the position of medical records in malpractice is proving as documentary evidence as stipulated in Government Regulation No. 26 of 1960 on Oath pronunciation Doctor, Article 187 of the Criminal Procedure Code as well as evidence statements of the experts as defined in Article 186 Criminal Procedure Code. Medical records serve as one form of health care in accordance with the applicable standards in the field of health. Not made of medical records by physicians will lead to doctors could be dragged to court to account for his actions (negligence) and will get imprisonment or a fine as stipulated in Article 79 clause (b) of Law Number 29 Year 2004 regarding Medical Practice and administrative measures in the form of verbal warning, written reprimand to revoking licenses as provided for in Article 17 Regulation of the Minister of Health No. 269 of 2008.